Eurosceptic, Eurocritical or Euroconfused? An analysis of the Five Star Movement's voting behaviour in the European Parliament. Issue 3 (27th May 2019) - Salvati, Eugenio
ABSTRACT: After two years of presence within the European Parliament (EP), is it possible to define the Five Star Movement (M5S) position regarding the European Union? Are these stances similar or different from the rhetoric used by the party leadership about EU? And which are the parties in the EP with which it shares similar policy positions? As a matter of fact, there is a certain confusion in defining Grillo's Movement position about European integration. The aim of the article is to enquire whether the M5S is taking political stances similar to those of Eurosceptic (and right wing) parties or if it is showing a different inclination, more similar to those assumed by pro Europe or Euro critical parties of the left and the new left. To accomplish this task, the article will take into consideration the M5S' voting behaviour within the EP on several policy areas which are salient for the European Union policy making. The first part of the article will be focused on the explanation of the M5S's growth and to the review of the concept of Euroscepticism. In the last part the M5S's votes concerning the policies related to the pro/anti integration, GAL/TAN and Left/Right cleavages, will be compared to the ones expressed by the Eurosceptic and leftist parties within the EP, to understand with which group there is the highest agreement rate. Thanks to the evidence produced it will be possible to define: (a) to which part of the EP political spectrum the M5S is closer, (b) provide a first in depth and descriptive analysis of the M5S' political behaviour within the supranational arena.